Obesity awareness in Latin America in health centers using a decision tree - Chuctaya Ruiz, Diego Moises (2024)
This paper seeks to raise awareness about localized obesity in Latin America and its health centers, inciting to reduce obesity in the population, taking as a tool a software that from the data taken in the research can determine the levels of obesity in a patient and recommend some ways to improve health using techniques related to Artificial Intelligence where the model applied to the data can be observed which are the people with a higher degree of obesity and analyze their respective causes.